Adoptive Management Innovation - Lin, Haifen (Springer Singapore, 2018)
This book discusses adoptive management innovation, which has been successfully implemented in other areas. It proposes a theory on this field by considering the importance and popularity of adoptive management innovation in China and around the globe, and focusing on its nature. It also establishes a process framework through which adoptive management innovation occurs, explores how individual characteristics of individual managers affect their adoption decision, examines the effects of a firm's dynamic capability on each phase of adoptive innovation, and addresses how intangible management innovation supports the process of tangible product innovation to produce effects. By exploring the process, adoption decision, drivers and effects of adoptive management innovation, the book offers abundant applications for managerial practice.